The Critical Management of Spinal Cord Injury: A Narrative Review - Emilio Moreno-González; Antonio Ibarra (Clinics and Practice)
Spinal cord injury (SCI) is defined as physical damage that alters the function and structure of the spinal cord. Traumatic causes, such as vehicle accidents, falls, and violence, account for 90% of SCI cases. Recent evidence suggests that early intensive care unit (ICU) monitoring improves patient prognosis, highlighting the importance of prompt ICU admission and early decompression surgery. This review includes 50 publications selected based on specific criteria to gather evidence on the current management of SCI in acute settings. Pharmacological agents have been studied for their neuroprotective properties, offering hope for improved neurological outcomes. Several clinical trials are evaluating new pharmacological alternatives for SCI. In conclusion, the current management of acute SCI should focus on standardized treatments addressing ventilatory, cardiopulmonary, and hematologic complications, all of which directly impact long-term neurological and functional prognosis. New neuroprotective agents currently in clinical trials show promising results and should be further studied to determine their role in acute SCI management.